School Committee Program to Improve Teacher's Performance in the District of Cipayung City Administration East Jakarta (CIPP Model Evaluation Research) - Udit,; Zulela,; Boeriswati, Endry (International Journal of Scientific Research and Management (IJSRM), 2020)
This research aims to evaluate the school committee program in improving the performance of Elementary School teachers in Cipayung sub-district. Method used evaluation study method with CIPP model. The results showed; (1). Context, the purpose of establishing a school committee consisting of channeling, responsible, transparent, accountable, and democratic. But there are no specific schedules to absorb the aspirations of the community, (2). Input, the implementation of recruitment of members of Cipayung Subdistrict School Committee is not fully done through the procedures established by the legislation, the Electoral Committee of prospective members of Cipayung Subdistrict School Committee is not formed and established by the principal but by members of the school committee of Cipayung Subdistrict, (3) Process, implementation of the function of the school committee, the implementation of the school committee duties, and the implementation of the school committee's role has been good, but schools have not maximally worked with the business and industrial World, (4) Product, performance enhancement consisting of better education services, completion of tasks, professionals in carrying out their roles and functions and improving student achievement. Conclusion has not been a similarity of concept of work and there are differences of perception about role and function of school committee.